Essays on the determinants of success of crowdfunding projects - TAN, Yee Heng (Institutional Knowledge at Singapore Management University, 2018)
Crowdfunding is a method of raising funds to support a venture, typically by raising small amounts from a large number of investors (backers or patrons). This whole process is conducted on an online platform that facilitates interactions between project creators and potential contributors. We explore in the dissertation, the determinants of the success of crowdfunding projects. The first essay, using data from Kickstarter (the leading crowdfunding platform), explores how backers to a project are interconnected with other backers through their backing of common projects thus forming an implicit backer network. We find that backers that are in central positions within the network have an impact on other backers and, through them, affect the outcomes of projects by increasing the likelihood of project success, increasing funding and decreasing the time taken to reach the funding goal. The second essay explores the unique phenomenon of patronage. Unlike the one-time contribution that backers make in Kickstarter, patrons fund the creator and their projects in a recurring manner. We use data from a leading patronage crowdfunding platform to explore what project characteristics lead to changes in patterns of patron growth and recurring contributions in crowdfunding. We find that several project characteristics not only have an impact on the change in patron and contribution functions but also in the velocity and acceleration of these functions. Both essays uncover determinants that have not been considered thus far in their respective crowdfunding context and provide recommendations for project creators and platforms to maximize the funding generated within each specific context.